RADIATION AND FORMATION SCENARIO OF ANISOTROPIC DARK ENERGY GRAVASTARS - Al-Asy'ari, Hasan
In this thesis, we study about one of alternatives to black holes, namely the gravastar proposed by Pawel O. Mazur and Emil Mottola (MM) in 2002 [1]. This study focuses on a gravastar whose interior is anisotropic. This is because based on the research of Cattoen et al., gravastars must have anisotropic pressures [2]. Two aspects are studied in this thesis. The first one is related to stability of radiating anisotropic gravastars model and the second one is related to the formation scenario of anisotropic gravastars. In the first study–based on our model–stable conditions of radiating anisotropic gravastars can be obtained in the case of dark energy and repulsive phantom energy interiors with a combination of standard or repulsive phantom thin shells. Then in the second study, it is found that in the transition phase (slowing-down) from the collapsing phase to the gravastar phase, the energy density ?, the radial pressure pr and the tangential pressure pt are inhomogeneous. The inhomogeneity of the three quantities is possible due to a significant transition from isotropic conditions to anisotropic conditions. In addition, these three quantities are also very dependent on the properties of the final phase (gravastar) to be formed. This means that gravastar transition scenarios will generally be different for gravastars with different interior properties.